Structural characterization and biological evaluation of uracil-appended benzylic amines as acetylcholinesterase and carbonic anhydrase I and II inhibitors - Bulut, Zafer; Abul, Nurgul; Poslu, Ayse Halic; Gulcin, Ilhami; Ece, Abdulilah; Ercag, Erol; Koz, Gamze (Elsevier, 2023)
A series of novel uracil-appended benzylic amines were synthesized through reductive amination with moderate to good yields (30-84% yields). In situ prepared 5-(arylidene)-6-aminouracils with the condensation reaction between 5,6-diamino-1,3-dimethyluracil and substituted salicylaldehydes were reduced by excess sodium borohydride. All of the compounds were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy and elemental analysis. The inhibition abilities of novel uracil-appended benzylic amines (1-9) were evaluated against acetylcholinesterase (AChE) and human carbonic anhydrase I and II (hCA I and II) isoenzymes that are linked to some global disorders such as Alzheimer's disease (AD), epilepsy, diabetes and glaucoma. The compounds exhibited inhibition profiles with K-i values ranging from 2.28 +/- 0.41 nM to 5.25 +/- 0.75 nM for AChE, 36.10 +/- 5.22-110.31 +/- 54.81 nM for hCA I and 16.33 +/- 4.91-72.03 +/- 28.86 for hCA II. Tacrine was used as a reference inhibitor for AChE and exhibited a K-i value of 2.59 +/- 0.92 nM against the AChE enzyme. On the other hand, Acetazolamide was used as a standard inhibitor towards hCA I and hCA II isoforms with K-i values of 31.38 +/- 8.56 nM and 18.72 +/- 1.67 nM, respectively. The results of enzyme inhibition associated with some global metabolic diseases indicate that novel uracil-appended benzylic amines may have the potential to develop new drugs to treat some common diseases such as Alzheimer's disease (AD), epilepsy and glaucoma. Molecular docking simulations were conducted to explain the binding interactions of compounds with AChE, hCA I and hCA II. Pharmacokinetic profiles were predicted to be within the acceptable ranges. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: Benzylic amines; Uracil; Reductive amination; Acetylcholinesterase; Carbonic anhydrase; Molecular docking